Equilibrium Selection and Public-Good Provision: The Development of Open-Source Software. - Myatt, D; Wallace, C (2002)
Collective-action problems arise in a variety of situations. Open-source software is a recent and important example. Copyright restrictions on open-source projects stipulate that any user may modify the software so long as any resulting innovation is freely available to all. In economic parlance, the innovation is a public good. The economic theory of public-good provision raises a number of important questions. Who contributes to such a project, and who free rides? How might a social planner exploit the interdependence of project components to encourage contributions? Under what conditions will such actions result in successful provision? Using a simple game-theoretic framework and recent results from the study of equilibrium selection, we attempt to answer these questions. Under reasonable assumptions of asymmetry and less than complete information, the most efficient providers will contribute. Contributions can be elicited by "integrating" the provision process when providers are sufficiently optimistic about the success of the project. Otherwise, the social planner may be better off "separating" the components so that individual contributions are independent of each other. The analysis yields recommendations for the leaders of open-source projects and other similar collective-action problems.